Best Practices for Designing Educational Mobile Applications - Dengen, Alvianus; Tserendorj, Baatar; Bayarmaa, Tsolmon (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The increasing reliance on mobile technology in education has led to the rapid development of educational mobile applications. However, many of these applications fail to effectively support learning due to poor design, lack of pedagogical alignment, and limited user engagement. Ensuring that mobile applications adhere to best practices in educational technology is crucial for enhancing learning outcomes and user experience. This study aims to identify and analyze best practices for designing educational mobile applications that optimize usability, engagement, and pedagogical effectiveness. A qualitative research approach was employed, incorporating a systematic literature review and expert interviews to evaluate key design principles. Findings indicate that successful educational mobile applications integrate user-centered design, adaptive learning strategies, gamification elements, and evidence-based pedagogical frameworks. Furthermore, accessibility features and interactive interfaces play a significant role in fostering learner motivation and retention. The study concludes that adherence to these best practices can significantly enhance the effectiveness of educational mobile applications. Implementing user-driven design, personalization, and interactive learning mechanisms ensures greater engagement and improved learning outcomes. Future research should focus on evaluating the long-term impact of these design principles on diverse learner populations and educational settings.